Trade Wars : What Do They Mean? Why Are They Happening Now? What Are the Costs? - Mattoo, Aaditya; Staiger, Robert W. (World Bank, Washington, DC, 2019)
How should economists interpret current trade wars and the recent U.S. trade actions that have initiated them? This paper offers an interpretation of current U.S. trade actions that is at once more charitable and less forgiving than that typically offered by economic commentators. More charitable, because under this interpretation it is possible to see a logic to these actions: the United States is initiating a change from "rules-based" to "power-based" tariff bargaining and is selecting countries with which it runs bilateral trade deficits as the most suitable targets of its bargaining tariffs. Less forgiving, because the main costs of these trade tactics cannot be avoided even if they happen to "work" and deliver lower tariffs. Rather, the paper shows that the main costs will arise from the use of the tactics themselves, and from the damage done by those tactics to the rules-based multilateral trading system and the longer-term interests of the United States and the rest of the world.